2017
DOI: 10.1111/cas.13324
|View full text |Cite
|
Sign up to set email alerts
|

CD155, an onco‐immunologic molecule in human tumors

Abstract: CD155 is the fifth member in the nectin‐like molecule family, and functions as the receptor of poliovirus; therefore, CD155 is also referred to as necl‐5, or PVR. As an immunoglobulin‐like adhesion molecule, CD155 is involved in cell motility, and natural killer and T cell‐mediated immunity. CD155 is barely or weakly expressed in various normal human tissues, but frequently overexpressed in human malignant tumors. CD155 overexpression promotes tumor cell invasion and migration, and is associated with tumor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 59 publications
2
131
0
Order By: Relevance
“…37 CD226 is upregulated in PVR knock-out mice and anti-PVR antibodies cause T-cell CD226 upregulation in wild-type mice. 38 TIGIT is a coinhibitory receptor expressed on T and NK cells 32,39,40 and, similar to CD226, has NECTIN2 and PVR ligands (Figure 3). 26,27 In a cellline model, TIGIT outcompetes CD226 for the PVR ligand.…”
Section: Figurementioning
confidence: 99%
“…37 CD226 is upregulated in PVR knock-out mice and anti-PVR antibodies cause T-cell CD226 upregulation in wild-type mice. 38 TIGIT is a coinhibitory receptor expressed on T and NK cells 32,39,40 and, similar to CD226, has NECTIN2 and PVR ligands (Figure 3). 26,27 In a cellline model, TIGIT outcompetes CD226 for the PVR ligand.…”
Section: Figurementioning
confidence: 99%
“…Functionally, CD155 interacts with nectin‐3 to regulate cell adhesion and migration . CD155 is overexpressed in human cancers . It has been reported that CD155 overexpression promotes cell migration and proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…However, since this balance is often disturbed in the tumor microenvironment and accumulating data suggest that PVR overexpression induces the immune escape of tumor cells, strategies targeting PVR might direct the immune response toward the elimination of tumor cells. 6,[11][12][13][14][15] Based on these findings, several different approaches based on PVR and its interactions are being explored in the field of antitumor therapy and are described in this review.…”
Section: Introductionmentioning
confidence: 99%